Family Guide to the National Insurance Scheme ([London] : His Majesty's Stationery Office, 1948)
1948 1948 1940s 32 pages : illustrations Allowance when she has finished drawing her Widow's Allowance. The Widowed Mother's Allowance is at the rate of 33s. 6d. a week for the mother and child together, and will last so long as the child is under school leaving age. If the widow is working the Widowed Mother's Allowance will be reduced by 1s. for every 1s. she earns above 30s. in any week. 34. Widow's Pension. A widow may get a Widow's Pension at the rate of 26s. a week in any of the following ways : (а) when Widow's Allowance ends, if she was over 50 when her husband died and had been married for ten years : (b) when Widowed Mother's Allowance ends, if she is then over 40 and ten years have passed since the date of her marriage ; (c) if, at the time when either Widow's Allowance or Widowed Mother's Allowance ends, she is unable to support herself because of some mental or bodily infirmity which is likely to remain with her for a long time. If the widow is working, the Widow's Pension will be reduced by 1s. for each 1s. she earns above 30s. in any week. Widows aged 60 or over get Retirement Pension instead of Widow's Pension. 35. Widows Who are Now Pensioners. If you already have a Widow's Pension you may be able to claim in its place from 5th July 1948 either a Widowed Mother's Allowance or the special pension for widows suffering from an infirmity. If so, and you have not already made a claim, you should ask for information at the Area Office of the Assistance Board (after 5th July 1948 at your National Insurance Office). 36. Married Women Covered by the Present Scheme. A 22 345/3/2/10